PENGARUH PUASA SUNNAH DAUD TERHADAP KECERDASAN EMOSIONAL MAHASISWA MA’HAD AL-HUSAIN BIN ‘ALI - Sabirin B. Syukur; Euis Hidayat (-, 2021)
Emotional intelligence is needed to be able to hold someone solve problems and overcome things that are around him. Puasa Daud can have a positive impact on the psyche, mental retention, self-control, stress control, and psyhophysical therapy. Purpose of research; To know the influence of Puasa Daud on Emotonal Intelligence of Ma’had Al-Husain bin’Ali Muhammadiyah University of Gorontalo. The design of this study used Pre Experiment with One Group Pre-test and Post-test design. Sample of 15 respondents. The result of the research using Paired T-Test statistic test showed emotonal intelligence after done the fasting teratment daud got sig value. 0,000 (p <0.05). the conclusion in this research is that there is influence of Puasa Daud to Emotional Intelligence of Ma’had Al-Husain bin ‘Ali Muhammadiyah University of Gorontalo.